Gestión administrativa- operativa y su incidencia en la rentabilidad de la empresa cerámicos al costo, Santo Domingo, periodo 2013-2014, plan de mejoramiento del proceso operativo. - Cedeño Cornejo, César Daniel (2015)
The operational – administrative management of the organizations related to construction industry looking to expand business operations, allowing them to be dynamic and competitive, in order to achieve positive financial returns to stay in the market, and are today part of the local economy which cooperates with the economic development significantly, under the great impulse that is offered to the construction industry in Santo Domingo. The primary objective of this thesis was to evaluate the incidence of the operational – administrative management the profitability of the Cerámicas al Costo company of Santo Domingo, performing an updated assessment of both the operational – administrative management as applying profitability indices for financial years 2013 and 2014. For this information research methods are used such as the method of analysis and inductive - deductive, because through the surveys of domestic partners as well as business customers could obtain the necessary information. Finally, after the evaluation of the operational – administrative management and in terms of achieving the estimated financial results achieved in each financial period it was essential to develop a plan for improvement in the operating process that allowed all your staff stay focused on the mission and vision of the company, knowing their responsibilities for each of their jobs and actively participate in periodic training.